2019
DOI: 10.1002/bbb.2013
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm cultivation and production in South America: status and perspectives

Abstract: South America is responsible for 16% of the world's agricultural production and 21% of the world's livestock. Palm harvesting has been gaining special attention, with constant growth in Brazil, Colombia, and Ecuador. Fast expansion in palm plantations in the equatorial zone around the world has been motivated by an increase in farming of species such as Elaeis guineensis, Elaeis oleifera, and Elaeis odora. Parallel to the increase of oil-palm harvesting, the generation of residues is an important aspect to tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
(11 reference statements)
0
1
0
1
Order By: Relevance
“…Regarding Paraguay, it was reported that the country has 11 ethanol production plants; however, these are first generation plants, so the residues are not used, but rather the harvest of agricultural crops (Ministerio de Obras Públicas y Comunicaciones de Paraguay, 2019 ). Finally, in Venezuela, it was found that there is a study under development for the production of ethanol from lignocellulosic residues such as cassava bagasse and sugarcane straw (Melendez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Paraguay, it was reported that the country has 11 ethanol production plants; however, these are first generation plants, so the residues are not used, but rather the harvest of agricultural crops (Ministerio de Obras Públicas y Comunicaciones de Paraguay, 2019 ). Finally, in Venezuela, it was found that there is a study under development for the production of ethanol from lignocellulosic residues such as cassava bagasse and sugarcane straw (Melendez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Assim, as gerações dos biocombustíveis podem ser observadas tanto na síntese do etanol, quanto do biodiesel (ambos de 1ª, 2ª, 3ª e 4ª geração) (Rezende & Pasa, 2017;Singh et al, 2020). Por meio dessa classificação, as tecnologias empregadas nos processos de pesquisas e produção, podem ser divulgados organizadamente no meio científico, proporcionando o compartilhamento de informações e avanços para o setor (Medina et al, 2019). Deste modo, cada geração subsequente de biocombustíveis representa uma evolução decorrente da geração anterior, ou seja, são avanços científicos (Da Silva et al, 2021).…”
Section: Introductionunclassified
“…Affording local communities the right to manage and restore forests may be a promising option to align global agendas for conservation, climate mitigation, and sustainable development [9,10]. In the NEA, the expanding African oil palm monocultures and large-scale cattle grazing are recognized as drivers of land-use change [11]. However, the poor socioeconomic indices in the region also undermine the conservation of the Amazon forest.…”
Section: Introductionmentioning
confidence: 99%